Gazing at the ultraslow magnetar in RCW 103 with NuSTAR and Swift. Issue 1 (2nd May 2018) - Borghese, A; Coti Zelati, F; Esposito, P; Rea, N; De Luca, A; Bachetti, M; Israel, G L; Perna, R; Pons, J A
Abstract: We report on a new NuSTAR observation and on the ongoing Swift X-Ray Telescope monitoring campaign of the peculiar source 1E 161348–5055, located at the centre of the supernova remnant RCW 103, which is recovering from its last outburst in 2016 June. The X-ray spectrum at the epoch of the NuSTAR observation can be described by either two absorbed blackbodies ($kT_{\rm BB_1}$  ∼ 0.5 keV, $kT_{\rm BB_2}$  ∼ 1.2 keV) or an absorbed blackbody plus a power law ($kT_{\rm BB_1}$  ∼ 0.6 keV, Γ ∼ 3.9). The observed flux was ∼9 × 10 −12  erg s −1  cm −2, ∼3 times lower than what observed at the outburst onset, but about one order of magnitude higher than the historical quiescent level. A periodic modulation was detected at the known 6.67 h periodicity. The spectral decomposition and evolution along the outburst decay are consistent with 1E 161348–5055 being a magnetar, the slowest ever detected.